Apropiación del social media marketing en la empresa del sector turístico de Morelia, Michoacán, México - Madrigal Moreno, Salvador (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Digital inclusion in Mexico has led various sectors, including tourism, to adopt the Internet as a channel of communication with its consumers. This research focuses on the study of how companies in the tourism sector of Morelia (CTSM) have adopted information and communication technologies (ICT) for the establishment, development and improvement of their marketing strategies in social media, in the city of Morelia. The main objective of this doctoral research was to determine the influence of information, investment, individualization, interaction, integration, and intention in the social media marketing of the CTSM; as well as knowing the appropriation of the social media in the CTSM. Therefore, this research presents a general model to be tested based on the study of literature in relation to three constructs: appropriation, relationship marketing and social media. It highlights the relevance of relationship marketing as theoretical support given that market conditions have changed and new relationships, networks and interaction have been given a new meaning. The theoretical model proposed was based on the review of the literature and is based on the model of the 6 I proposed by Diller (2000), and the classic dyad (the relationship between the provider and the client) of Gummesson (2008). Subsequently, an instrument was developed to measure the relationship of the constructs of the proposed theoretical model. To contrast the model, primary information was collected from a random, representative, and proportional sample of 148 companies in the tourism sector of Morelia registered in the National Registry of Tourism (NRT).

La inclusión digital en México ha propiciado que diversos sectores, entre ellos el turismo, haya adoptado a Internet como canal de comunicación. Esta investigación se centra en estudiar cómo las empresas del sector turístico de Morelia (ESTM) han adoptado las tecnologías de la información y la comunicación (TIC) para el establecimiento, desarrollo y mejoramiento de sus estrategias de marketing en social media, en la ciudad de Morelia. El objetivo general de esta investigación doctoral fue: determinar la influencia de la información, inversión, individualización, interacción, integración, e intención en el social media marketing de la ESTM; además de conocer la apropiación del social media en la ESTM. Por lo tanto, en esta investigación se presenta un modelo general a comprobar basado en el estudio de la literatura en relación a tres constructos: la apropiación, el marketing relacional y el social media. Destaca la pertinencia del marketing relacional como sustento teórico dado que han cambiado las condiciones del mercado y se ha brindado de un nuevo significado a las relaciones, las redes y la interacción. El modelo teórico propuesto se configuró a partir de la revisión de la literatura y se basa en el modelo de las 6 I propuesto por Diller (2000), y la díada clásica (la relación entre el proveedor y el cliente) de Gummesson (2008). Posteriormente, se elaboró un instrumento para medir la relación de los constructos del modelo teórico propuesto. Para contrastar el modelo se recabó información primaria de una muestra aleatoria, representativa y proporcional de 148 empresas del sector turístico de Morelia registradas en el Registro Nacional de Turismo (RNT).
Facultad de Contaduría y Ciencias Administrativas. Doctorado en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-D-2018-1537; Marketing relacional; Social media; Apropiación; Turismo; PLS-SEM; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1082